Simultaneous Bioreduction of Multiple Oxidized Contaminants Using a Membrane Biofilm Reactor. (1st February 2017) - Li, Haixiang; Lin, Hua; Xu, Xiaoyin; Jiang, Minmin; Chang, Chein‐Chi; Xia, Siqing
ABSTRACT: : This study tests a hydrogen‐based membrane biofilm reactor (MBfR) to investigate simultaneous bioreduction of selected oxidized contaminants, including nitrate ( ‐N), sulfate ( ), bromate ( ), chromate (Cr(VI)) and para ‐chloronitrobenzene ( p ‐CNB). The experiments demonstrate that MBfR can achieve high performance for contaminants bioreduction to harmless or immobile forms in 240 days, with a maximum reduction fluxes of 0.901 g ‐N/m 2 ·d, 1.573 g /m 2 ·d, 0.009 g /m 2 ·d, 0.022 g Cr(VI)/m 2 ·d, and 0.043 g p ‐CNB/m 2 ·d. Increasing H2 pressure and decreasing influent surface loading enhanced removal efficiency of the reactor. Flux analysis indicates that nitrate and sulfate reductions competed more strongly than, Cr(VI) and p ‐CNB reduction. The average H2 utilization rate, H2 flux, and H2 utilization efficiency of the reactor were 0.026 to 0.052 mg H2 /cm 3 ·d, 0.024 to 0.046 mg H2 /cm 2 ·d, and 97.5% to 99.3% (nearly 100%). Results show the hydrogen‐based MBfR may be suitable for removing multiple oxidized contaminants in drinking water or groundwater.